Effectiveness and Safety of JAK Inhibitors in Autoinflammatory Diseases: A Systematic Review - Boyadzhieva, Zhivana; Ruffer, Nikolas; Burmester, Gerd; Pankow, Anne; Krusche, Martin (Frontiers in Medicine, 2022)
Autoinflammatory diseases (AID) are rare diseases presenting with episodes of sterile inflammation. These involve multiple organs and can cause both acute organ damage and serious long-term effects, like amyloidosis. Disease-specific anti-inflammatory therapeutic strategies are established for some AID. However, their clinical course frequently includes relapsing, uncontrolled conditions. Therefore, new therapeutic approaches are needed. Janus Kinase inhibitors (JAKi) block key cytokines of AID pathogenesis and can be a potential option. A systematic review of the literature in accordance with the PRISMA guidelines was conducted. Three databases (MEDLINE, Embase and Cochrane Central Register of Controlled Trials) were searched for publications regarding the use of JAKi for AID. Data from the included publications was extracted and a narrative synthesis was performed. Criteria for defining treatment response were defined and applied. We report data from 38 publications with a total of 101 patients describing the effects of JAKi in AID. Data on Type I Interferonopathies, Adult-Onset Still´s Disease (AOSD), Systemic Juvenile Idiopathic Arthritis (sJIA), Familial Mediterranean Fever (FMF), and Behçet’s Syndrome (BS) was identified. From a total of 52 patients with type I interferonopathies, in seven patients (7/52, 13.5%) a complete response was achieved, most (35/52, 67.3%) showed a partial response and a minority (10/52, 19.2%) showed no treatment response. For AOSD, a complete or a partial response was achieved by eleven (11/26, 42.3%) patients each. Two sJIA patients achieved complete response (2/4, 50%) and in two cases (2/4, 50%) a partial response was reported. Half of FMF patients showed a complete response and the other half had a partial one (3/6, 50.0%). Amongst BS patients most achieved a partial response (8/13, 61.5%). Five patients showed no response to therapy (5/13, 38.5%). Overall, the most frequent AEs were upper respiratory tract infections (17), pneumonia (10), BK virus viremia (10) and viruria (4), herpes zoster infection (5), viral gastroenteritis (2) and other infections (4). The results from this systematic review show that JAKi can be beneficial in certain AID. The risk of AEs, especially viral infections, should be considered. To accurately assess the risk benefit ratio of JAKi for AID, clinical trials should be conducted.